Contributions of atmospheric plasma treatment on a hygrothermal aged carbon/epoxy 3D woven composite material. (August 2022) - Gillet, Camille; Hassoune-Rhabbour, Bouchra; Poncin-Epaillard, Fabienne; Tchalla, Tatiana; Nassiet, Valérie
Highlights: Hygrothermal ageing causes various phenomena on the composite material surfaces, which can be problematic for achieving good bonding. Atmospheric plasma treatment allows, despite slight thermal degradation, to chemically activate unaged and aged surfaces by oxygen grafting. Desorption is found on the aged treated surfaces because of the thermal action of plasma. Abstract: In this paper, the effects of hygrothermal ageing and atmospheric plasma surface treatment on a 3D carbon/epoxy-amine woven composite material are studied. The goal is to study the surface evolution of the materials in terms of chemical composition and morphology. Plasma treatment is applied on new and hygrothermally aged samples in order to analyse its contribution to the surface modifications and degradations. It appears that hygrothermal ageing has irreversible absorption behaviour causing hydrolysis, oxidation and particle losses, which modifies the surface chemistry and topology. On the other hand, the atmospheric plasma causes oxidation of the matrix. Indeed, when a repair is necessary, the damaged part could evolve due to moisture absorption related to ageing. As the fibres are exposed, the topology and surface chemistry are modified. Nevertheless, it allows to desorb the humidity adsorbed on the surface and reach an oxidation level similar to unaged treated samples.